Qualitative Aspect of Internationalization in Ukrainian Higher Education - Iryna Myhovych (Vasyl Stefanyk Precarpathian National University, 2019)
The article represents an attempt to investigate qualitative aspect of internationalization process within the context of Ukrainian system of higher education. Internationalization has been viewed as a reaction to the global transformation processes, as well as a unique possibility for Ukrainian higher education to ensure its integrated transformation according to European and world trends. Based on the research on the theory of internationalization, international education, overseas recruitment and mobility, issues of quality in higher education have been discussed, as well as a number of practical rationales for internationalization of higher education applicable within the context of Ukrainian higher education system have been outlined. Based on the rationales educational outcomes of internationalization in Ukrainian higher education have been substantiated.